(untitled) - Allen, Robert G. (New York, 1983)
Programmed to think that saving is good, debt and risk-taking bad, we disqualify ourselves from ever having a chance at big money. The first step in creating wealth is to stop thinking poor. Then you're ready to create your own version of the Allen plan, keyed to integrating real estate with other wealth-generating investments.
Keywords: Tài chính, cá nhân,Finance, personal